PERAN BADAN AMIL ZAKAT NASIONAL DALAM PEMBANGUNAN DAN PENGEMBANGAN PENDIDIKAN DI BULUKUMBA - Jabal Nur; Siti Aisyah; Musyfikah Ilyas (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2024)
The focus of this research is on the utilization of zakat in the field of education by the National Amil Zakat Agency (BAZNAS) in Bulukumba and the challenges it faces in the management and distribution of zakat funds in Bulukumba. This research is a field study, descriptive in nature, with an empirical juridical and sharia approach. The results show that the role of zakat in the development and enhancement of education in Bulukumba, managed by BAZNAS Bulukumba, can be seen from the effectiveness of educational programs, which include assistance for study completion, tuition assistance for underprivileged and high-achieving students, provision of uniforms and school supplies for students, distribution of smart bag packages for impoverished students, assistance for tahfiz teachers, renovation and construction of pesantren (Islamic boarding schools) and madrasah (Islamic schools), mosque renovation assistance, and more. Through these assistance programs, educational development in the Bulukumba region has progressed, helping to reduce or prevent school dropouts, neglect, illiteracy, and the lack of formal education among children.